Faktor-Faktor yang Dipertimbangkan Konsumen Untuk Membeli Mobil Toyota Avanza ( Studi Kasus pada PT Agung Automall di Kota Denpasar) - Dewi, Ida Ayu Brahmaika Praba; Jatra, I Made (E-Jurnal Manajemen, 2013)
The research objective is to determine and analyze the factors that consumers consider in deciding to buy a Toyota Avanza at PT Agung AutoMall in Denpasar. This research was conducted at PT Agung AutoMall in Denpasar with a sample of 140 people using accidental sampling technique. Obtained five factors are considered against the decision to buy a Toyota Avanza at PT Agung AutoMall in Denpasar with a variance of 70.938 percent. These five factors are: (1) marketing mix factors, the faktor loading of 13.331 and has a variance equal to 47.609 percent, (2) social factors, with a faktor loading of 2,280 and has a variance equal to 8.143 percent; (3) The price factor, with faktor loading of 1.681 and has a variance equal to 6.005 percent, (4) psychological factors, the faktor loading of 1,489 and has a variance equal to 5.319 percent, and (5) produkdengan factor faktor loading of 1.162 and has a variance equal to 4.152 percent Keywords: Factor - Factor, Decision, Consumer, Buying, Cars